Transformação digital de micro e pequenas empresas de setores criativos : uma análise dos setores audiovisual, música e publicidade de Juiz de Fora. - Vasconcelos, Paula Bento de (2019)
The constant changes in the economic and social environment oblige micro and small companies to adapt quickly to the scenarios presented by the new economy, marked by the processes digitalization, innovative mindset, disruption in the business model and centralization of the customer's role in the consumption process. Adaptation is a slogan and, faced with this reality, concepts such as digital transformation and creativity gain relevance as strategic assets for companies to position themselves in the market. This work aims to identify how Juiz de Fora's micro and small businesses in creative sectors (audiovisual, music and advertising) are adapting to the new scenario and experiencing the digital transformation of their businesses and, based on this, propose a taxonomy that is able to classify in which stage a company is in that process, when analyzed under the aspects of the domains of digital transformation, proposed by Rogers (2017). The research was carried out in two stages, a quantitative one with 207 questionnaires answered by entrepreneurs of the studied sectors and a qualitative step, with the accomplishment of interviews with 15 entrepreneurs. As a result of the research, a taxonomy of the digital transformation of micro and small companies was proposed, consisting of 5 categories: customer network, competition, data, innovation and value, and 15 subcategories that make it possible to classify the maturity of a company in the transformation journey digital. The applicability of the obtained results is observed in favor of the identification and the organization of the processes related to the transformation of the businesses, so that managers can, in analyzing their positions, structure strategies so that they have better and better results